Development of Picture and Picture-Based Science Learning Modules in Elementary Schools - Sepvianti Liana Charty; Harlinda Syofyan (Journal of Educational Sciences, 2024)
The research conducted aims to determine the steps taken in the development of teaching materials in the form of Picture and Picture based learning modules on human respiratory system materials and to determine the level of validity of teaching materials developed. This research is a type of Research and Development (R&D) which refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this study were grade V students of SDN Serdang Wetan. This research data was obtained by observation, interviews, and questionnaires. The results of the study obtained a material expert validation value of 90% with very valid criteria, media expert validation of 76.6% with valid criteria, and linguists of 80% with valid criteria, the results of module assessment by teachers obtained very valid criteria with a percentage of 90.9%. In small group trials, learning modules obtained a percentage of 87.3% with very valid criteria and large group trials obtained a percentage of 91.3% with very valid criteria.